Issues in pharmacy education. - Abdul Razak, Tariq (IIUM Press, 2011)
The practice of pharmacy differs in different countries. Similarly pharmacy education differs in addressing the needs of the practice. In some countries there is a clear separation of dispensing and prescribing between pharmacists and the physician, in others this separation is not that clear cut. In certain countries pharmacists are not allowed at all to examine patients and this may even be an offence under the law